Mangokal Holi (Kajian Antropologi Simbolik Pada Etnis Batak di Desa Pagar Jati, Kec. Lubuk Pakam) - Winanda, Putri; Dora, Nuriza (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research examines the Mangokal Holi ceremony of the Batak Toba tribe which is carried out in the Pagar Jati village, Lubuk Pakam sub-district as a form of respect for deceased ancestors. Mangokal Holi is a ceremony (exhumation of bones). Mangokal Holi (digging up skeletons) is a unique tradition of the Toba Batak tribe. The tradition of dismantling and moving skeletons to a more suitable location has continued since the time of the ancestors of the Batak tribe. This research aims to find out the procedures for carrying out the Mangokal Holi ceremony as a symbol of the Toba Batak tribe in the village of Pagar Jati, sub-district. deep into the grave. In this research, researchers used qualitative research with ethnographic methods. The main subjects of this research are local residents. The data collection techniques used were observation and interviews. The results of this research are that not all village communities perform the Mangokal Holi ceremony because the costs required are quite large so that all communities can afford to do it. The symbols contained in the Mangokal Holi ceremony are Martonggoraja, ulos penampin, mangombak, kaffir lime juice, white cloth. , and stone na pear. The time period for carrying out the mangokal Holi ceremony is around 10-15 years as a form of respect for the ancestors. The structure of the Mangokal Holi event is tinopat ma aka hula-hula ni si okalon, martonggo raja, reading prayers, the grave digging process, bone handover ceremony, mangokal Holi ceremony.